Rapid immunomagnetic negative enrichment of neutrophil granulocytes from murine bone marrow for functional studies in vitro and in vivo. - Mike Hasenberg; Anja Köhler; Susanne Bonifatius; Katrin Borucki; Monika Riek-Burchardt; Julia Achilles; Linda Männ; Kathleen Baumgart; Burkhart Schraven; Matthias Gunzer (PLoS ONE, 2011)
Polymorphonuclear neutrophils (PMN) mediate early immunity to infection but can also cause host damage if their effector functions are not controlled. Their lack or dysfunction is associated with severe health problems and thus the analysis of PMN physiology is a central issue. One prerequisite for PMN analysis is the availability of purified cells from primary organs. While human PMN are easily isolated from peripheral blood, this approach is less suitable for mice due to limited availability of blood. Instead, bone marrow (BM) is an easily available reservoir of murine PMN, but methods to obtain pure cells from BM are limited. We have developed a novel protocol allowing the isolation of highly pure untouched PMN from murine BM by negative immunomagnetic isolation using a complex antibody cocktail. The protocol is simple and fast (~1 h), has a high yield (5-10*10⁶ PMN per animal) and provides a purity of cells equivalent to positive selection (>80%). Most importantly, cells obtained by this method are non-activated and remain fully functional in vitro or after adoptive transfer into recipient animals. This method should thus greatly facilitate the study of primary murine PMN in vitro and in vivo.